Spatial Identifications and Strategies toward Creative Village in Bandar Lampung City - Persada, Citra; Nandang, Nandang; Nugroho, Agung Cahyo (International Series on Interdisciplinary Science and Technology, 2019)
Urban village as a historic village has a high physical, social and cultural values that needs to be preserved. Kampung Negeri Olok Gading has been designated as a cultural and historical village by the Government of Bandar Lampung City, however it is constrainted by the development of the surrounding area. The purposes of this study are: (1) to know the pattern and variety of activities within the village as a creative village embryo; (2) to know the physical condition, functional condition and environmental condition of the kampung; (3) to formulate the physical arrangement strategy in transforming Kampung Negeri Olok Gading become Urban Creative Village. This research uses descriptive analysis methodology through empirical study to existing condition. Through empirical tracking of the physical elements of the area, it is known that there are significant changes to the condition of the urban village such as: the changing of land use and building, the changing of the building and the environment. The main strategy that can be applied to transform Kampung into the creative village is the integrated conservation of the area which include physical, social and cultural aspects